Can machine learning help solve credit spread puzzle? - Vastamäki, Eemeli (My University, 2022)
The goal of this thesis is to study the applicability of machine learning models in predicting credit spreads. The focus of the thesis is on US corporate bonds and their credit spreads with US government bonds. The main result of the thesis is that it is possible to use machine learning models to improve prediction accuracy when compared to the more traditional Longstaff– Schwartz (1995) model. In addition to the empirical analysis, the thesis includes a literature review on credit risks and machine learning. The literature review examines previously used models and previously conducted empirical analyses. The literature review related to credit risks reviews the structural models used in the study of credit risks. The section focusing on machine learning studies how machine learning methods, especially neural networks, have previously been used in option pricing. The thesis's empirical analysis is motivated by the credit spread puzzle. The credit spread puzzle refers to a situation where traditional credit risk models cannot accurately predict the spread between corporate bonds and risk-free interest rates. The credit spread puzzle has been found in some studies specifically in loans with a high credit rating, but in some studies also with loans with a lower credit rating. Explanations for the credit spread puzzle include, among other things, that the spreads are affected by other risk drivers than default risk alone, such as the liquidity of the loan. In the empirical section of the thesis, the Longstaff–Schwartz model is first calibrated to the available price observations. As a result of the calibration, the prediction accuracy is already improved by changing the original parameters of the model. After the calibration, the results of the structural model are compared to those from the machine learning models. The results indicate that the machine learning models improve prediction accuracy when compared to the structural model. The regularization methods used in the machine learning models also improve the prediction accuracy when compared to the traditional neural network model.

Tämän tutkielman tarkoituksena on selvittää koneoppimismenetelmien soveltuvuutta korkoerojen ennustamisessa. Tutkielman pääpaino on yhdysvaltalaisissa yrityslainoissa ja näiden korkoeroissa Yhdysvaltojen valtionlainoihin. Tutkielman päätuloksena on, että koneoppimismenetelmillä on mahdollista parantaa ennustetarkkuutta perinteisempään Longstaff–Schwartz (1995) malliin verrattuna. Empiirisen analyysiin lisäksi tutkielmassa on kirjallisuuskatsaus luottoriskeistä sekä koneoppimisesta. Kirjallisuuskatsauksessa selvitetään aiemmin käytettyjä malleja sekä aiempia empiirisiä analyysejä. Luottoriskeihin liittyvässä kirjallisuuskatsauksessa tutkitaan luottoriskien tutkimisessa käytettyjä rakenteellisia malleja, ja koneoppimiseen keskittyvä osuus selvittää, miten koneoppimismenetelmiä – varsinkin neuroverkkoja – on aiemmin käytetty optiohinnoittelussa. Tutkielman empiirinen analyysi motivoidaan korkoeroilmiöllä (englanniksi credit spread puzzle). Korkoeroilmiö viittaa tilanteeseen, jossa perinteiset luottoriskimallit eivät pysty ennustamaan tarkasti yrityslainojen ja riskittömän koron välistä eroa. Korkoeroilmiö on havaittu osassa tutkimuksissa nimenomaan korkean luottoluokituksen lainoissa, mutta joissain tutkimuksissa myös alemman luottoluokituksen lainoissa. Korkoeroilmiön syiksi on esitetty muun muassa sitä, että eroihin vaikuttaa laiminlyöntiriskin lisäksi myös muita tekijöitä, kuten lainan likviditeetti. Ensimmäisenä tutkielman empiirisessä osiossa Longstaff–Schwartz malli kalibroidaan hintahavaintoihin. Kalibroinnin tulokseksi saadaan, että mallin alkuperäisiä parametrejä vaihtamalla voidaan jo parantaa ennustetarkkuutta. Kalibroinnin jälkeen vuorossa on rakenteellisen mallin sekä koneoppimismenetelmien tulosten vertailu. Tuloksista selviää, että koneoppimismallit parantavat ennustetarkkuutta rakenteelliseen malliin verrattuna. Koneoppimismallissa käytetyt regularisaatio menetelmät myös parantavat ennustetarkkuutta perinteiseen neuroverkkomalliin verrattuna.
Keywords: Machine learning, credit spreads, neural networks